Symposium 3: Content and Language Integrated Learning: Shifting Boundaries and Terrain Mapping - Hunter, Moira; Parchoma, Gale (Proceedings of the International Conference on Networked Learning, 2024)
European policies mandate encouraging plurilingualism in a digitally enhanced world. This mandate is placing increased demands on higher educational practitioners and institutions to prepare today’s learners with new linguistic skills. Content and Language Integrated Learning (CLIL) policy appears to resonate strongly with European aspirations and goals of educating citizens and promoting lingual diversity, pluriculturism, and mobility within the European Union. Whilst offering a potential solution through the interweaving of content and language in a dual-focused educational approach, CLIL is at risk of becoming a ‘buzz word’ without evidence-based research on emerging CLIL practices. This paper suggests a framework for practice-based research in the initial steps of CLIL implementation into HE curriculum and considers expansive learning theory as a theoretical and analytical framework to advance knowledge creation. The deliberate construction of a transciplinary networked learning community is advanced as the outcome and vehicle as the first initiative for CLIL implementation. The partnering and convergence of the knowledge expertise of language experts and subject experts in collaborative reflective practice enhances networked learning within and beyond the institutional boundaries, professional development and learner multiliteracies, including languages, culture, content and digital media. The context for this study is within tertiary architectural education in France where students study architecture in the first language, French, and Language and Communication Skills in the additional language of English as a separate discipline. This lack of convergence appears at odds with the emerging trend and evolution of transdisiplinarity in architectural education and practice where academia and associated professions of architecture, design and engineering increasingly teach, practice and research collaboratively. This desk-based research first examines the significance of CLIL in the European context, its variants, along with the challenges and drawbacks in crossing disciplinary boundaries. The implications for language and disciplinary practitioners and their role are discussed. Transdisciplinary collaborative work, teaching and learning can bridge language and knowledge barriers between the different disciplines in and through the fusion of language learning of, for, and through the languages of architectural practice and content, leading to innovation in curriculum development. Relational agency, in other words calling on the capacity of individuals to jointly work and learn with other practitioners, pedagogies, theories and resources distributed within institutional settings, given that a supportive learning community is possible, can lead to enhanced professional agency, in other words the capacity to act effectively informed by appropriate professional knowledge.. This paper concludes that further research is needed on relational agency within collective activities, such as networked learning communities to advance CLIL implementation.